Analysis of electrochemical noise with phase space methods. - Aldrich, Chris; Qi, B.; Botha, P. (Elsevier, 2006)
Analysis of the apparently random fluctuations in the current and potential of freely corroding systems has long been seen as a promising approach to the development of better corrosion sensors. Apart from the rate of corrosion, electrochemical noise signals also contain information on the nature of the corrosion system. This is crucially important in the monitoring of localized corrosion, where the rate of corrosion can be a poor predictor of the potential damage to structures. Unfortunately, assessment of the typically complex corrosion dynamics from electrochemical noise can be difficult, and has met with partial success only over the last three decades or so. In this paper, the use of phase space methods as a basis for monitoring corrosion systems is considered. The correlation dimensions of the corroding systems are used as a discriminating statistics and preliminary experiments are discussed.